2013
DOI: 10.5343/bms.2012.1041
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of El Niño/La Niña–Southern Oscillation Variability in the Neogene-Pleistocene of Panama Revealed by a New Bryozoan Assemblage-Based Proxy

Abstract: Here we explore how fossil cheilostome bryozoans can demonstrate El Niño/La Niña-Southern Oscillation (ENSO) variability in ancient tropical environments of the tropical eastern Pacific and southwestern Caribbean when used collectively to produce frequency distributions of estimates of mean annual ranges in temperature (MARTs) via zooid-size MART analysis (zs-MART). The approach is based on linking variation in the sizes of constituent zooids in bryozoan colonies with the temperature regimes in which the zooid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Excluding sample B, non-TDA MART was 6.6 °C and the MART observed across all samples was 6.2 °C. These values are consistent with those found by Okamura et al (2013), who reported a MART of 6.1 °C, and Jackson and O'Dea (2013), who found MARTs around 6 °C throughout the Miocene based on a bryozoan zooid size proxy. These values are also similar to the MART of 6° C found at 50 m water depth in modern upwelling TEP waters, while SWC waters have a MART of 4 °C (World Ocean Atlas2001, Conkright et al 2002, Tao et al, 2013.…”
Section: Paleoenvironmental Implications Of Isotopic Analysessupporting
confidence: 91%
“…Excluding sample B, non-TDA MART was 6.6 °C and the MART observed across all samples was 6.2 °C. These values are consistent with those found by Okamura et al (2013), who reported a MART of 6.1 °C, and Jackson and O'Dea (2013), who found MARTs around 6 °C throughout the Miocene based on a bryozoan zooid size proxy. These values are also similar to the MART of 6° C found at 50 m water depth in modern upwelling TEP waters, while SWC waters have a MART of 4 °C (World Ocean Atlas2001, Conkright et al 2002, Tao et al, 2013.…”
Section: Paleoenvironmental Implications Of Isotopic Analysessupporting
confidence: 91%
“…It is best exposed along the Rabo de Puerco river in Armuelles, where a complete section of different fossil horizons can be crossed by walking a couple of kilometers upstream from where it intersects the road (8º 16.801'N, 82º 51.995'W) . At the base of the section you can find large boulders that still retain abundant oysters, corals and bryozoans (Okamura et al (2013)). Going up the section, you can find a wide bed of bivalve mollusks of the Pinna genus with exceptionally well-preserved specimens of this large filter mollusk ( Figure 055).…”
Section: Lexiconmentioning
confidence: 99%
“…Molnar (2008) suggested that differences in salinity do not of themselves require closure of the seaway connection between the oceans that might also be explained by a shift from a permanent El Niño-like state to the modern El Niño-Southern Oscillation (ENSO) state today. However, the hypothesis that the TEP experienced permanent El Niño conditions in the Pliocene (Wara et al 2005) remains unresolved (see Rickaby and Halloran 2005, von der Heydt et al 2011, Okamura et al 2013, and the question remains as to what would have caused such a large-scale shift in climatic regimes in the first place?…”
Section: Paleoceanographic Evidencementioning
confidence: 99%